Where are modern flow techniques heading to? - Horstkotte, Burkhard; Miró, Manuel; Solich, Petr (Analytical and bioanalytical chemistry, 2018)
This article aims to provide an overview on the transition from earlier laboratory automation using analytical flow approaches toward today's applications of flow methodologies, recent developments, and future trends. The article is directed to flow practitioners while serving as a valuable reference to newcomers in the field in providing insight into flow techniques and conceptual differences in operation across the distinct flow generations. In the focus are the recently developed and complementary techniques Lab-On-Valve and Lab-In-Syringe. In the following, a brief comparison of the different application niches and contributions of flow techniques to past and modern analytical chemistry is given, including (i) the development of sample pretreatment approaches, (ii) the potential applicability for in-situ/on-site monitoring of environmental compartments or technical processes, (iii) the ability of miniaturization of laboratory chemistry, (iv) the unique advantages for implementation of kinetic assays, and finally (v) the beneficial online coupling with scanning or separation analytical techniques. We also give a critical comparison to alternative approaches for automation based on autosamplers and robotic systems. Finally, an outlook on future applications and developments including 3D prototyping and specific needs for further improvements is given. Graphical abstract ᅟ.
Keywords: Lab-On-Valve and Lab-In-Syringe; Flow techniques; Monitoring and surveillance; Automation and miniaturization; Hyphenation; Sample pretreatment